Forest pattern and ecological process : a synthesis of 25 years of research - Lindenmayer, David (CSIRO Pub., 2009)
2010 Whitley Certificate of Commendation for Zoological TextForest Pattern and Ecological Process is a major synthesis of 25 years of intensiveresearch about the montane ash forests of Victoria, which support the world's tallestflowering plants and several of Australia's most high profile threatened and/orendangered species. It draws together major insights based on over 170 publishedscientific papers and books, offering a previously unrecognised set of perspectivesof how forests function. The book combines key strands of research on wildfires, biodiversity conservation, logging, conservation ma.